APPLICATION OF INTEGRAL EVALUATION SCALES IN PATIENTS WITH WIDESPREAD PURULENT PERITONITIS - Лещишин, Ярослав Миронович; Баранов, Андрей Игоревич; Потехин, Константин Владимирович; Ярощук, Сергей Александрович; Валуйских, Юрий Викторович (Medicine in Kuzbass, 2020)
An objective assessment of the severity of the patient’s condition allows for a comparative study of their results and, equally important, a more objective prediction of treatment outcomes. In our work, we use several scales to assess the severity of patients with advanced purulent peritonitis and predict the mortality of patients in the sample, these are SAPSII, SOFA, MODS and MPI. Aim – compare the prognostic value of the above scales in patients with advanced purulent peritonitis. Materials and methods. We studied the medical records of patients who were treated with the diagnosis: common purulent peritonitis in the period from 2013 to 2018. A retrospective analysis of the severity of patients condition was performed using the SAPSII, SOFA, MODS scale and the Mannheim peritonitis index (MIP). According to the selected inclusion and exclusion criteria, 184 cases histories were selected. The gender distribution is 90 mans (48.9 %) and 94 females (51.1 %). The median age is 63 years (25% – 52, 75% – 75). Statistical processing included methods of nonparametric statistics and ROC analysis. Results. The median score of the MIP scale for all patients in the sample was 26 (21; 30) points, in the group of patients with a favorable outcome it was 23 (17; 26) points, in the group of patients with a fatal outcome – 30 (26; 34) points, the differences are statistically significant (U = 7.4; p < 0.001). The tendency to increase mortality with an increase in MIP scores is statistically significant (χ2CA = 42.4; p < 0.001). The median score of the SAPSII scale for all patients in the sample was 32 (21; 52) points, in the group of patients with a favorable outcome it was 26 (18; 33) points, in the group of patients with a fatal outcome – 57 (48; 71) points, the differences are statistically significant (U = 9.6; p < 0.001). The tendency to increase mortality with increasing SAPSII scores is statistically significant (χ2CA = 95.9; p < 0.001). The median score of the SOFA scale for all patients in the sample was 4 (2; 7) points, in the group of patients with a favorable outcome it was 2 (1; 4) points, in the group of patients with a fatal outcome – 8 (5; 11) points, the differences are statistically significant (U = 8.0; p < 0.001). The tendency to increase mortality with increasing scores on the SOFA scale is statistically significant (χ2CA = 74.9; p < 0.001). The median score of the MODS scale for all patients in the sample was 3 (1; 5) points, in the group of patients with a favorable outcome it was 1 (0; 3) points, in the group of patients with a fatal outcome – 6 (4; 8) points, the differences are statistically significant (U = 8.2; p < 0.001). The tendency to increase lethality with increasing MODS scores is statistically significant (χ2CA = 59.5; p < 0.001). All scales have a statistically significant predictive ability (p<0.001 for the Mann-Whitney test). When predicting mortality for a specific patient, the SAPSII scale has the best predictive ability, the overall accuracy of the forecast was 90 %, 85 % of cases with a fatal outcome and 94 % of cases with a favorable outcome were correctly predicted, the AUROC indicator is 0.94. The accuracy of the forecast for the rest of the scales are of the order of 79-81 %. Conclusion. Thus, the use of integral scales in assessing the severity of patients with widespread purulent peritonitis is justified. Collecting the necessary data to assess the severity of the condition is available in almost any hospital providing emergency surgical care and allows you to statistically reliably predict the outcome of the disease.